Fake news w dobie post-prawdy. Teoria i praktyka - Bożek, Małgorzata (Dydaktyka Polonistyczna, 2019)
Century is a time of a media revolution. Convergence, networking and massive digitalization of culture caused that traditional kind of media are changing its aspect and structure but not only. In addition, their impact on reality is much more stronger than several decades ago. The changes that are happening now in media affect much more than just our everyday life. Those, that are mentioned in article let us ask questions about existence of truth as a unquestionable value that is widely respected and defined as a basis for the functioning of democratic societies.